The mesopelagic anoxic Black Sea as an unexpected habitat for Synechococcus challenges our understanding of global "deep red fluorescence" - Callieri, Cristiana; Slabakova, Violeta; Dzhembekova, Nina; Slabakova, Nataliya; Peneva, Elisaveta; Cabello-Yeves, Pedro J; Di Cesare, Andrea; Eckert, Ester M; Bertoni, Roberto; Corno, Gianluca; Salcher, Michaela M; Kamburska, Lyudmila; et al. (The ISME journal, 2019)
The Black Sea is the largest meromictic sea with a reservoir of anoxic water extending from 100 to 1000 m depth. These deeper layers are characterised by a poorly understood fluorescence signal called "deep red fluorescence", a chlorophyll a- (Chl a) like signal found in deep dark oceanic waters. In two cruises, we repeatedly found up to 103 cells ml-1 of picocyanobacteria at 750 m depth in these waters and isolated two phycoerythrin-rich Synechococcus sp. strains (BS55D and BS56D). Tests on BS56D revealed its high adaptability, involving the accumulation of Chl a in anoxic/dark conditions and its capacity to photosynthesise when re-exposed to light. Whole-genome sequencing of the two strains showed the presence of genes that confirms the putative ability of our strains to survive in harsh mesopelagic environments. This discovery provides new evidence to support early speculations associating the "deep red fluorescence" signal to viable picocyanobacteria populations in the deep oxygen-depleted oceans, suggesting a reconsideration of the ecological role of a viable stock of Synechococcus in dark deep waters.
Keywords: genom bakteriální; ekosystém; Fluorescence; oceány a moře; fykoerythrin; fluorescence; fotosyntéza; Černé moře; Chlorophyll A; Synechococcus; Photosynthesis; fylogeneze; chlorofyl a; Phycoerythrin; Ecosystem; Genome, Bacterial; Phylogeny; Black Sea; Oceans and Seas